Creative Entrepreneurship Learning Model Based On Local Wisdom Through Carrot Bean Sprout Spring Roll Innovation In Science Learning Grade 4 - Switaningsih H, Christiana; Lusiana, Rosalia Eka; Sulianto, Joko (Schola, 2024)
Introducing local wisdom to elementary school students is an important step in creating a generation that knows their own culture. The introduction of local wisdom involves not only understanding traditions, but also the introduction of cultural products that have economic value, such as specialty foods. The purpose of this study is to develop entrepreneurial skills, critical thinking, and innovate independently through the product “Lumpia Wortel Tauge”. This model is designed to introduce the concept of edupreneurship by combining the material of natural resource utilization in science learning and the introduction of local wisdom through the process of making spring rolls. This research used a descriptive qualitative method. Data collection techniques used observation, interview, and questionnaire to measure active participation, collaboration among students, understanding of nutrition, and product production and promotion skills. The results showed that practice-based learning in spring roll making can improve students' understanding of science concepts as well as basic entrepreneurial skills. Thus, students are not only consumers of products, but also learn to be creative producers who appreciate local cultural heritage and understand the importance of healthy eating. The results recommend that students can learn entrepreneurship by utilizing local wisdom and adding innovation as a development product. Carrot bean sprouts spring rolls are a new potential that can develop practical entrepreneurial skills for students of SD Pangudi Luhur Santo Yusup.